Neuromyelitis Optica in a Young Woman With Tuberous Sclerosis: Is There an Association? - Mahmoud Elkhooly MD; Jacob Rube MD; Samiksha Srivastava MD; Shitiz Sriwastava MD; Robert Lisak MD; Evanthia Bernitsas MD (SAGE Publishing, 2022)
Tuberous sclerosis complex (TSC) is a genetic neurocutaneous disorder that presents with multi-organ involvement, including but not limited to hamartomas in the brain, eyes, heart, lung, liver, kidney, and skin. Neuromyelitis optica spectrum disorder (NMOSD) is an inflammatory, autoimmune, demyelinating, central nervous system disorder, targeting the optic nerves and spinal cord. We report a 30-year-old woman with TSC who developed tingling in the legs that gradually involved her abdomen. Additional symptoms included severe vomiting that lasted for a week and spasms in her legs. One month later, she was hospitalized due to difficulty ambulating and tingling in her hands. Magnetic resonance imaging (MRI) of her spine showed longitudinally extensive upper cervical and lower thoracic cord signal changes. MRI scan of her brain showed few non-specific T2 signal changes along with cortical and subcortical tubers. Aquaporin (AQP4) IgG antibody was found to be positive in both serum and cerebrospinal fluid. Accordingly, she was diagnosed with NMOSD, treated with a 5-day course of intravenous steroids, followed by 5 sessions of plasma exchange. After her initial improvement, she was started on rituximab as maintenance therapy. Two years later, she is clinically stable, and her follow-up MRI showed marked improvement.